Intravenous neridronate for skeletal damage treatment in patients with multiple myeloma - Pittari, G.; Costi, D.; Raballo, et al., M. (Acta Biomedica Atenei Parmensis, 2006)
Almost 70-80% of the patients with Multiple Myeloma (MM) in advancer phase, of the disease show osteolytic lesions and/or pathologic fractures, with or without secondary osteoporosis. An accelerated osteoclast-mediated bone absorption is believed to be the main cause of bone damage in MM. Osteoclast can be activated by a variety of microenvironmental factors. Bisphosphonates (BF) induce the apoptosis of osteoclasts and inhibit osteoclastogenesis, thus preventing bone absorption. As well as BFs, the so-called secondgeneration BF (N-BF) may impair the activity of osteoclast. Neridronic acid (NER) is a N-BF molecule officially registered for the treatment of osteogenesis imperfecta. Nevertheless, NER has shown a remarkable efficacy in Paget’s disease, postmenopausal osteoporosis and, most recently, in androgen deprivation-treated prostatic carcinoma. The primary endpoint of this study was to evaluate hip and spine Bone Mineral Density (BMD) modifications over the 12-month treatment with NER in a group of patients affected by MM with evidence of initial skeletal damage. Secondary endpoints were (1) changes of calcium and total Alkaline Phosphatase (tAP) plasma levels during treatment with NER and (2) tolerability of 100 mg NER monthly administration for 12 months. These data suggest that NER, if administered at these doses and timing, might allow at least for one year sustained BMD increases in patients . NER has been highly tolerated in this study. The almost complete absence of adverse effects has prompted us to reduce the time of infusions at the end of the study. In conclusion, this study provides the first data on the efficacy and safety of NER in patients with MM-induced bone damage. These initial data encourage wider phase III trials to clearly assess its efficacy in preventing skeletal-related events and its possible anti-neoplastic properties.